Anthropology with Activism: Settling Its Value. (September 2014) - Hull, Glynda A.
<x xml:space="preserve">Abstract</x> This response to Katherine Schultz's Presidential Address to the Council on Anthropology and Education explores the themes of temporality and reflexivity in activist scholarship, with Schultz's research as prime example. The need to take action to address a crisis, juxtaposed to the counter need to take time for scholarly reflection and theorizing, which threads through Schultz's address, inspires considerations of how today's anthropologically oriented research is being reconfigured in relation to space and time.